Правове забезпечення публічних та приватних інтересів у фауністичному праві України в контексті права власності на тваринний світ - Шеховцов В.; Shekhovtsov V (Волин. нац. ун-т. ім. Лесі Українки, 2020)
Статтю присвячено висвітленню публічно-приватних засад у процесі регламентування відносин щодо приналежності на об’єкти тваринного світу. Досліджено міждисциплінарний статус права власності на тваринний світ, який визначається нормами цивільного (приватного) й екологічного (публічного) права. На підставі узагальнення наукової доктрини, автор підтримує існуючі напрацювання та обґрунтовує необхідність оптимального збалансування цих інтересів, а в разі виникнення конфлікту інтересів – пріоритетом наділяти публічні інтереси, які спрямовані на раціональне використання об'єктів тваринного світу, збереження популяцій диких тварин і місць їх проживання зокрема, і забезпечення сприятливої екологічної обстановки в світі в цілому. The article examines the main issues of ownership of the animal world and its objects through the lens of public and private property. The fauna is a unique natural resource, and the species, physiological, and biological characteristics of animals determine the interdisciplinary nature of the legal regulation of social relations in the sphere of belonging to the fauna. The distinction between the spheres of influence of civil (private) and environmental (public) law is important both theoretically and practically to ensure the realization of the respective interests of the participants in public relations. The author supports the existing scientific doctrines, generalizes them, justifies the need for optimal balancing of these interests, and argues that in case of conflict of interests, the priority is on the side of the public interests, which are aimed at the rational use of wildlife, the conservation of wildlife populations and their habitats in particular, and ensuring a favorable ecological environment in the world as a whole.
Legal Support of Public and Private Interests in the Law on Fauna of Ukraine: the Context of the Right to Ownership of Fauna
Keywords: право власності на тваринний світ; публічна власність; приватна власність; публічно-приватні засади права власності на тваринний світ; екологічні інтереси; ownership of fauna; public property; private property; public-private principles of ownership of fauna; ecological interests